2003
DOI: 10.1034/j.1600-0528.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries incidence rates in Swedish adolescents and young adults with particular reference to adjacent approximal tooth surfaces: a methodological study

Abstract: The caries rate of an approximal tooth surface was 1.6-32.3 times higher if the adjacent surface was in a caries state compared to when the latter was sound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…The results from the surface level analyses mirrored the results from the subject level analysis. An advantage of the surface level analyses was that they confirmed the differing susceptibility of approximal surfaces to caries progression found in other studies [Dummer et al, 1988;Mejàre et al, 1999;Hintze, 2001;Stenlund et al, 2003]. This paper also illustrated the need for statistical analysis to account for the clustering of surfaces within subjects that has been reported in other studies.…”
Section: Discussionsupporting
confidence: 54%
“…The results from the surface level analyses mirrored the results from the subject level analysis. An advantage of the surface level analyses was that they confirmed the differing susceptibility of approximal surfaces to caries progression found in other studies [Dummer et al, 1988;Mejàre et al, 1999;Hintze, 2001;Stenlund et al, 2003]. This paper also illustrated the need for statistical analysis to account for the clustering of surfaces within subjects that has been reported in other studies.…”
Section: Discussionsupporting
confidence: 54%
“…For the unfilled surfaces, the risk increased if the adjacent surface had a caries lesion. This finding is similar to the findings of Stenlund et al [2003] and may reflect the fact that both surfaces belong to the same approximal area, and this area may be a caries-susceptible site, possibly due to difficulties in plaque removal. For previously filled surfaces, the status of the adjacent surface seemed to be of less importance, a tendency however indicated that if the adjacent surface was filled or filled and carious, then the risk of developing a caries lesion was increased.…”
Section: Discussionsupporting
confidence: 79%
“…The study demonstrated that the caries rate of an approximal tooth surface was 1.6-32.3 times higher if the adjacent surface had a caries lesion [Stenlund et al, 2003]. In a Danish study the effect of iatrogenic preparation damage on the need for operative caries treatment adjacent to class II restorations was evaluated, and it was concluded that the risk of developing a caries lesion was higher in surfaces which had experienced preparation damage [Qvist et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Caries are visible clinically before they can be observed in radiographic images because a certain degree of demineralization of the enamel must occur before they are visible in an X-ray (36). The resolution of the CT scans used here was clearly higher than the resolution that allows more accurate detection of periapical lesions compared with the resolution of periapical radiographs (37).…”
Section: Discussionmentioning
confidence: 99%